Run-time mapping techniques for NoC-based heterogeneous MPSoC platforms - Singh, Amit Kumar. (2013)
The reliance on Multi-Processor Systems-on-Chip (MPSoCs) to satisfy the high performance requirement of complex embedded software applications is increasing. The Networks-on-Chip (NoCs) based interconnection infrastructure is fast becoming a preferred approach to facilitate communication among the processing elements (PEs) of MPSoCs. The heterogeneity of MPSoCs is also increasing by employing diﬀerent types of PEs in order to meet the functional and non-functional requirements. This necessitates the need to realize eﬃcient run-time mapping techniques for such heterogeneous computing platforms.